Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Tarif terhadap Kepuasan Pasien RSUD dr. Mohamad Soewandhie Surabaya - Mira Gayatri Kartika; Ony Kurniawati; Dyah Pelitawati; Indah Citra Anifia (Jurnal Simki Economic, 2025)
This research is focused on analyzing the relationship between cost, quality of service, and product quality with patient satisfaction at RSUD Dr. Mohamad Soewandhie Surabaya. The main issue addressed is the low level of patient satisfaction, which may affect the hospital’s image and future service utilization decisions. A total of 115 respondents were selected using a quantitative approach and descriptive analysis with a non-probability sampling technique. The respondents were general (paying) patients who visited the hospital. Data analysis indicated that patient satisfaction is significantly influenced by cost, service quality, and product quality, both in partial and simultaneous analyses. These three factors explained 34% of the variance in patient satisfaction based on the coefficient of determination (R²). The findings suggest that improvements in cost efficiency, service, and product quality have a direct impact on satisfaction, which in turn affects patient loyalty and the hospital's image. The remaining 66% is attributed to other variables beyond the scope of this study and requires further investigation.